1994
DOI: 10.1007/bf00154316
|View full text |Cite
|
Sign up to set email alerts
|

Permeabilization of Escherichia coli cells for enhanced penicillin acylase activity

Abstract: Escherichia coli cells with penicillin acylase activity were permeabilized with aqueous solutions of the cationic detergent N-cetyl-N,N,N-trimethylammonium bromide (CTAB), at pH 8.0 and the activity was found to have almost doubled. The concentration of CTAB, the time and temperature of treatment were optimised for maximum enzyme activity and were found to be 0.2%, 20 min and 5'C respectively. Subsequently, the cell bound activity was retained for a longer period by chemical cross-linking with 0.1% glutaraldeh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…A method for complete inactivation of a microbial nitrilase transformant with GA has been developed that provides > 9-log reduction in viable cells without a significant decrease in nitrilase activity, thus avoiding containment and safety issues for handling, storage and transportation of live recombinant cultures. Although GA has been successfully employed to stabilize microbial glucose isomerase [9] and penicillin acylase, [10] it has also been reported that enzymes with a thiol functional group in or very near the active site of the enzyme (e.g., nitrilase) are inactivated by thiolreactive agents such as GA, [11] and use of GA to inactivate live cells while retaining microbial nitrilase activity was potentially problematic. [12] Preservation of nitrilase activity during GA treatment of the microbial nitrilase biocatalyst was dependent on reaction time, temperature, GA concentration, pH and the concentration of ammonia and other amines (e.g., amino acids and peptides) in the culture media that react with GA. A preferred GA treatment method reacted cells from high density fermentation (100-150 OD 550 ) with 5-10 wt% aqueous GA that was added with efficient mixing at 50 mg to 100 mg GA/L min À1 , resulting in a final concentration of about 3.5 g to 5 g GA/L (ca.…”
Section: Discussionmentioning
confidence: 99%
“…A method for complete inactivation of a microbial nitrilase transformant with GA has been developed that provides > 9-log reduction in viable cells without a significant decrease in nitrilase activity, thus avoiding containment and safety issues for handling, storage and transportation of live recombinant cultures. Although GA has been successfully employed to stabilize microbial glucose isomerase [9] and penicillin acylase, [10] it has also been reported that enzymes with a thiol functional group in or very near the active site of the enzyme (e.g., nitrilase) are inactivated by thiolreactive agents such as GA, [11] and use of GA to inactivate live cells while retaining microbial nitrilase activity was potentially problematic. [12] Preservation of nitrilase activity during GA treatment of the microbial nitrilase biocatalyst was dependent on reaction time, temperature, GA concentration, pH and the concentration of ammonia and other amines (e.g., amino acids and peptides) in the culture media that react with GA. A preferred GA treatment method reacted cells from high density fermentation (100-150 OD 550 ) with 5-10 wt% aqueous GA that was added with efficient mixing at 50 mg to 100 mg GA/L min À1 , resulting in a final concentration of about 3.5 g to 5 g GA/L (ca.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that there were no previous studies of the effect of DO on protein production during the maturation process. Nagalakshimi and Pai (1994) have reported that volumetric PA activity increased 2-fold Acetic acid concentration at the end of batch cultures increased from 0.35 to 1.5 g/L, as DO decreased from 40 to 0.2 %. To determine if the accumulated acetic acid was responsible for the observed increase in PA at low DO (Fig.…”
Section: Incubation Conditionsmentioning
confidence: 97%
“…Cell permeabilization can be used as an important tool in the biotransformation process that can enhance enzyme activity. Some reports show that the activities of intracellular enzymes could be improved significantly by permeabilization treatment (Decleire et al, 1987;Gough et al, 2001;Nagalakshmi & Pai, 1994). As an intracellular enzyme, whole cells of various microbial strains showed low levels of PAL activity on account of membrane permeability barriers for the substrate.…”
Section: Strategy Of Improving Pal Activitymentioning
confidence: 99%